Ivor Horton's beginning Visual C++ 2005 - Horton, Ivor (Wiley Pub, 2006)
Programming with Visual C++ 2005; Data, Variables, and Calculations; Decisions and Loops; Arrays, Strings, and Pointers; Introducing Structure into Your Programs; More about Program Structure; Defining Your Own Data Types; More on Classes; Class Inheritance and Virtual Functions; Debugging Techniques; Windows Programming Concepts; Windows Programming with the Microsoft Foundation Classes; Working with Menus and Toolbars; Drawing in a Window;...